2022
DOI: 10.1186/s13229-022-00526-1
|View full text |Cite
|
Sign up to set email alerts
|

Infant excitation/inhibition balance interacts with executive attention to predict autistic traits in childhood

Abstract: Background Autism is proposed to be characterised by an atypical balance of cortical excitation and inhibition (E/I). However, most studies have examined E/I alterations in older autistic individuals, meaning that findings could in part reflect homeostatic compensation. To assess the directionality of effects, it is necessary to examine alterations in E/I balance early in the lifespan before symptom emergence. Recent explanatory frameworks have argued that it is also necessary to consider how e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…This was the basis for development of the Q-CHAT 27,39 . There is also accumulating evidence across different modalities that infants who go on to receive a diagnosis of autism have differences in their neurobiology and physiology from as young as 6-9 months [63][64][65][66][67][68] Thus our work links emerging social cognitive profile relevant to ASD, also to dynamic functional connectivity at birth, especially within sensory networks. This correlation between higher scores on an instrument, which captures early features relevant to ASD (though not necessarily diagnostic) to the dynamics of sensory systems, is in agreement with the importance of sensory processes throughout the lifespan in individuals who have an ASD diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…This was the basis for development of the Q-CHAT 27,39 . There is also accumulating evidence across different modalities that infants who go on to receive a diagnosis of autism have differences in their neurobiology and physiology from as young as 6-9 months [63][64][65][66][67][68] Thus our work links emerging social cognitive profile relevant to ASD, also to dynamic functional connectivity at birth, especially within sensory networks. This correlation between higher scores on an instrument, which captures early features relevant to ASD (though not necessarily diagnostic) to the dynamics of sensory systems, is in agreement with the importance of sensory processes throughout the lifespan in individuals who have an ASD diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…Deviations in EI development in human infants could thus impact the processing of spectro-temporal speech information, which is, amongst others, crucial for phonemes (i.e., speech sounds) and pitch (involved in speech prosody and intonation). Some recent evidence suggests that autism is related to differences in EI balance already during infancy (Carter Leno et al, 2022), which could thus affect acoustic fine-tuning of the auditory cortex. It has recently been shown that electrophysiological processing of acoustic-phonological information in infancy predicts later language development (Menn, Ward, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The aperiodic slope becomes an increasingly popular index of the E/I ratio in neuropsychiatric and neurodevelopmental disorders, such as schizophrenia (Molina et al, 2020), attention deficit hyperactivity disorders (Arnett, Rutter, & Stein, 2022; Ostlund, Alperin, Drew, & Karalunas, 2021; Robertson et al, 2019), obsessive-compulsive disorder (Perera, Mallawaarachchi, Bailey, Murphy, & Fitzgerald, 2023), depression (Veerakumar et al, 2019), Rett syndrome (Roche et al, 2019), Fragile X syndrome (Wilkinson & Nelson, 2021) and autism spectrum disorders (Carter Leno et al, 2022). Many of these recent studies used EEG and estimated a single aperiodic slope in a broad frequency range (e.g.…”
Section: Discussionmentioning
confidence: 99%